If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 2 + -3 + 4x) = 2 Reorder the terms: 2(2 + -3 + x + 4x) = 2 Combine like terms: 2 + -3 = -1 2(-1 + x + 4x) = 2 Combine like terms: x + 4x = 5x 2(-1 + 5x) = 2 (-1 * 2 + 5x * 2) = 2 (-2 + 10x) = 2 Solving -2 + 10x = 2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 10x = 2 + 2 Combine like terms: -2 + 2 = 0 0 + 10x = 2 + 2 10x = 2 + 2 Combine like terms: 2 + 2 = 4 10x = 4 Divide each side by '10'. x = 0.4 Simplifying x = 0.4
| 3x(2x+5)+6x = | | -4(4p+3)=-44 | | 2x+12=-12-10x | | 5.5-2y=2.5-0.5y | | 720=-0.5x^2+50x-472 | | 3(4n-1)=45 | | 32+102+x+25=180 | | x^2+y^2-10+6y+27=0 | | 8a+25+7=0 | | 12t=48 | | 36x+16+3=15 | | x^2=63 | | 2r=68 | | -10n+18=-8n-10 | | 355x+2+159x=459-x | | 2x+4=150 | | 7c=56 | | 22-x=3(x+2) | | 75x^10-3x^8=0 | | -X^2-3=0 | | -x+4x-7=3-4x | | X^3-3=0 | | 5-(x+3)=20 | | 6x+2+8=16 | | -7c+6=-22 | | 3x(2x+5)+6x= | | -X^3-3x=0 | | 6(x+8)-2(x-4)=1 | | 4(-4+4x)=-64 | | (5x+6)(3x^2-7x+2)=0 | | 4x+2(x)=8 | | -4(4+2x)=-48 |